Pengaruh Kompetensi Sumber Daya Manusia, Sistem Informasi Pemerintah Daerah (SIPD), Sistem Pengendalian Intern Terhadap Kualitas Laporan Keuangan Pemerintah Daerah - Hardiyati Indah Nurpala, Siti; Fachruddin Arrozi, Muhammad (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2024)
This study aims to determine the effect of human resource competence, local government information systems, internal control systems on the quality of local government financial reports. The population in this study is the expenditure treasurer’s share of the SKPD in the Provincial Government of DKI Jakarta with a total of 42 SKPD. The data used is primary data with a quantitative descriptive approach obtained from respondents through distributing questionnaires. Therefore, the data analysis used is an analysis in the form of multiple linear regression tests. The results of this study indicate that, simultaneously on the variable competence of human resources, local government information systems and internal control systems have a significant effect on the quality of local government financial reports. This is evidenced by the results of the simultaneous test (Test F). And partially shows the results of human resource competencies, local government information systems and internal control systems have a significant effect on the quality of local government financial reports. This is proven from the partial test (t test).